Alandering Of Li-Ion Electrodes And Its Im-Pact On The Final Capacity Of Lithium-Ion Cell - Svoboda, Lukáš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
There is an effort to produce lithium-ion batteries with maximal density of energy, or higher capacity of cell with the same size. Calendaring of electrodes is important part of manufacturing of batteries. Its parameters, mainly the pressure of calendaring and with it related the final compression ratio of electrode layers, affect parameters of battery significantly. It is the process of pressing electrode material coated on current collector with certain pressure and it reduces its porosity and thickness. The aim of this article is determination of suitable level of calendaring that increases specific capacity, but does not reduce its cyclability.
Keywords: lithium-ion; LiFePO4; graphite; calendaring; capacity; galvanostatic cycling with potential limitation; electrochemical impedance spectroscopy